A comparative analysis on antibiotic resistance pattern in environmental and clinical bacterial isolates based on whole cell protein profiling by SDS-PAGE - Fatema, Aneeka Nawar (BRAC University, 2015)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2015